Keselamatan Nasabah Pinjaman Online dalam Perspektif Hukum Islam: Studi Kasus Berdasarkan Konsep Hifdz al-Mal dan Maqasid al- Shariah - Hakim, M. Abdul Rahman; Fatmawati, Nilal Muna; Kahfi, Nazih Sadatul; Lutfiyah, Lutfiyah (Journal of Sharia Economic Law, 2025)
This research aims to discuss the safety of online loan customers from the perspective of maqashid sharia, which aims to protect the interests and rights of individual people. In this context, maqashid sharia is a guideline to ensure that online loan products not only meet legal aspects according to the country, but must also be in line with ethics and morality as per maqashid sharia principles. The method used is library research, as it has been studied from various sources, such as previous books, laws, books and also related scientific articles. The research results show that the safety of online loan customers from a maqashid sharia perspective is very vulnerable, because online lending practices often result in injustice and economic exploitation, which is contrary to the principles of maqashid sharia. First, Hifdz Al-din emphasized the need for convenience and certainty in sharia muamalah for customers. Second, hifdz al-nafs demands an ethical and safe billing process for the physical safety of customers. Third, hifdz al-aql requires customer mental protection from detrimental withdrawal practices. Fourth, hifdz al-nasb guarantees that the collection process does not destroy the customer's family. Fifth, hifdz al-mal demands transparency of fees and fair interest. Thus, this research underlines the need for stricter regulations in the online lending industry to ensure the protection of customer rights in accordance with the maqashid of Sharia